2020
DOI: 10.1371/journal.ppat.1008555
|View full text |Cite
|
Sign up to set email alerts
|

Rapid in vitro generation of bona fide exhausted CD8+ T cells is accompanied by Tcf7 promotor methylation

Abstract: Exhaustion is a dysfunctional state of cytotoxic CD8+ T cells (CTL) observed in chronic infection and cancer. Current in vivo models of CTL exhaustion using chronic viral infections or cancer yield very few exhausted CTL, limiting the analysis that can be done on these cells. Establishing an in vitro system that rapidly induces CTL exhaustion would therefore greatly facilitate the study of this phenotype, identify the truly exhaustion-associated changes and allow the testing of novel approaches to reverse or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 68 publications
2
42
0
Order By: Relevance
“…These dominant transcriptional features are notably shared in a direct comparison of CD8 + T ex isolated from HIV-infected and melanoma patients. They can also be recapitulated in CD8 + T cells given repeated cognate peptide stimulations in vitro ( 26 , 27 ). However, significant disparities in CD8 + T ex transcriptional phenotypes also exist between cancer and viral settings.…”
Section: Translating Cd8 + T Cell Exhaustion From Chronic Infection To Cancer: a Common Role Of Persistent Antigenmentioning
confidence: 99%
“…These dominant transcriptional features are notably shared in a direct comparison of CD8 + T ex isolated from HIV-infected and melanoma patients. They can also be recapitulated in CD8 + T cells given repeated cognate peptide stimulations in vitro ( 26 , 27 ). However, significant disparities in CD8 + T ex transcriptional phenotypes also exist between cancer and viral settings.…”
Section: Translating Cd8 + T Cell Exhaustion From Chronic Infection To Cancer: a Common Role Of Persistent Antigenmentioning
confidence: 99%
“…It has been demonstrated that ectopic expression of TCF‐1 not only enhanced the function of Tex resulting in better control of chronic viral infection and preclinical tumors, 15,66 but also showed a pronounced impact on global chromatin accessibility and the transcriptome in Tex by increasing the expression of a series of transcription regulators associated with key effector function, including FOXO1, Zeb2, Id3, and Eomes, 15 or suppressing the expression of Blimp‐1 and Bim 66 . In contrast, TCF‐1 silencing during exhaustion is in part controlled by DNA methylation using a rapid in vitro system of CD8 + T cell exhaustion 67 . Based on this evidence, TCF‐1 as an attractive therapeutic target may be the key to broadly boost antiviral and antitumor immunity.…”
Section: Role Of Tcf‐1 In T Cell Exhaustionmentioning
confidence: 99%
“…66 In contrast, TCF-1 silencing during exhaustion is in part controlled by DNA methylation using a rapid in vitro system of CD8 + T cell exhaustion. 67 Based on this evidence, TCF-1 as an attractive therapeutic target may be the key to broadly boost antiviral and antitumor immunity. 4 | TCF-1-ASSOCIATED REGULATORY MOLECULES…”
Section: Role Of Tcf-1 In T Cell Exhaustionmentioning
confidence: 99%
“…In CD8 + T EX cells, the levels of TCF1 are substantially reduced. DNA methylation analysis of in vitro generated CD8 + T EX cells in a lymphocytic choriomeningitis virus (LCMV) infection-based model of T cell exhaustion has revealed that the promoter of the Tcf7 gene is hypermethylated, likely leading to the downregulation of TCF1 expression [ 19 ]. Similarly, previous studies have also suggested that TCF1 expression may be regulated through the control of chromatin accessibility [ 20 , 21 ].…”
Section: T Cell Factormentioning
confidence: 99%
“…However, a recent study into in vitro methods of T EX cell generation shows great promise for potential use. Using repeated antigen exposure in conjunction with IL-7 and IL-15 treatment, CD8 + T EX cells possessing characteristics similar to that of CD8 + T EX cells found in the LCMV exhaustion models were able to be generated [ 19 ]. While the nature of CD8 + T cell exhaustion varies between types of infections and human disease as well as amongst different types of tissue, such development of in vitro methods for exhaust T cell generation may be utilized as a means of accelerating an otherwise slow and inefficient field of T cell research [ 110 ].…”
Section: Conclusion: Challenges and Perspectivesmentioning
confidence: 99%